Here's the question you clicked on:
lilsis76
How can I re-write the sum's suing Sigma Notation for: 2 - 2^2 + 2^3 -2^4 +2^5 I know the reoccuring number is going to be 2 which goes to the right of the sigma. on the bottom of sigma it would be 1, and top of sigma would be 5 right?
\[\sum_{n=0}^{4}2(-2)^n\] is one way of writing it.
oh. so that (-2), is that how it would go from negative to positive?
expand what i wrote and check for yourself
okay: -2^0 = 0 *2 = 0 -2^1=-2*2=-4 -2^2=-4*2=-8 -2^3=-8*2=-16
@cnknd is this how it would go?
ur doing the exponents wrong... this is basics...
|dw:1353786706417:dw|okay the first one would be>....< @cnknd
in what i put down, the index n goes from 0 to 4... so it's 2(-2)^0 + 2(-2)^1 + 2(-2)^2 + 2(-2)^3 + 2(-2)^4 which is 2(1) + 2(-2) + 2(4) + 2(-8) + 2(16)
OH SHOOT! i just noticed i started at 1. i just now noticed it starts at 0
okay okay, i got it now. it makes more sense starting at zero haha thank you. Medal for you :)